Alterations in whole-brain dynamic functional stability during memory tasks under dexmedetomidine sedation - Liu, Lin-Lin; He, Jian-Long; Yuen, Vivian Man-Ying; Xu, Xuebing; Guan, Xuan; Qiu, Yan; Wang, Yingzi; Jian, Chao-Jun; Wen, Zhibo; Liu, Ke-Xuan (Frontiers in Neurology, 2022)
Purpose: Task-based and resting-state functional magnetic resonance imaging (fMRI) have been applied to investigate the neurobiological effects of dexmedetomidine using time-averaged static methods. Most of the previous fMRI studies of sedatives relied on conventional static functional connectivity approaches. Dynamic functional connectivity analysis may reveal the dynamic characteristic of brain activity during sedation. The purpose of this study was to explore the neurological effects of dexmedetomidine-induced sedation on memory using functional stability, a whole-brain voxel-wise dynamic functional connectivity approach. Methods: A total of 16 healthy participants (10 males) underwent auditory memory task-related fMRI in the awake state and under dexmedetomidine sedation. Explicit and implicit memory tests were conducted 4 h after ceasing dexmedetomidine administration. One-sample Wilcoxon signed rank test was applied to determine the formation of explicit and implicit memory in the two states. Functional stability was calculated and compared voxel-wise between the awake and sedated states. The association between functional stability and memory performance was also assessed. Results: Explicit and implicit memory formation was observed at baseline but not during dexmedetomidine sedation. Compared to that at wakeful baseline, functional stability during light sedation was reduced in the medial prefrontal cortex, left angular gyrus, and right hippocampus (all clusters, p < 0.05, GRF-corrected), whereas the left superior temporal gyrus (cluster p < 0. 05, GRF-corrected) exhibited higher functional stability. No significant associations were observed between functional stability and memory test scores. Conclusions: The distribution and patterns of alterations in functional stability during sedation illustrate the modulation of functional architecture by dexmedetomidine from a dynamic perspective. Our findings provide novel insight into the dynamic brain functional networks underlying consciousness and memory in humans.